Influence of continuous sugarcane cropping on chemical properties of clayer soils - da Silva, Maria Sonia Lopes; Ribeiro, Mateus Rosas (Pesquisa Agropecuaria Brasileira, 1995)
The objective of this work was to evaluate the effect of continuous sugarcane cropping on some chemical properties of low coastal plateau soils at Santa Clotilde Mill, Rio Largo, AL, Brazil. Four sites were selected involving a native vegetation area (TN) and sugarcane fields cultivated for periods of five (T5), fifteen (T15) and twenty-five (T25) years. The soils were morphologicaliy charac-terized and samples were taken from each horizon to determine pH, organic C, assimilable P, exchangeable bases, Al and H, cation exchange capacity, base saturation, and Al saturation. The results showed that in the soil studied under management conditions, sugarcane cropping provided a great improvement in soil fertility, contributing for the maintenance of organic matter, increase in pH, Ca, Mg and P levels, increase in bases saturation and decrease in Al saturation. Except for P, it was observed that great changes occurred on cultivated soils compared to a cultivated soils, but variations among cultivated soils were not found.